Plantation Economic Potential for enhancing Community Income - Diar Tangke; Dynne Andriany (Gorontalo Development Review, 2021)
In Assilulu village, Central Maluku district, the goal of this research was to determine the economic potential of plantations and approaches for increasing farmers' income. Qualitative methods and SWOT analysis tools also applied. The analysis indicated that the economic potential of plantations based on classical production factors was not maximized in terms of quantity of vegetable produce, and that the revenue earned from production could meet the demands of farmers. Farms are in quadrant II of the SWOT analysis, indicating that they have strength but have significant obstacles, so the recommendation is to implement a strategy.